Effects of Extracellular Vesicles Derived from Human Umbilical Cord Blood Mesenchymal Stem Cells on Cell Immunity in Nonobese Mice - Yang Ou; Yang Yang; Yan Wang; Heng Su; Yi-kun Zhou (Hindawi Limited, 2024)
Autoimmune responses are the most important pathogenic mechanisms underlying type 1 diabetes (T1D). Extracellular vesicles (EVs) derived from mesenchymal stem cells (MSCs) have immunomodulatory effects. In this study, we investigated whether EVs derived from human umbilical cord MSCs (HucMSC-EVs) have treatment effects on nonobese diabetic (NOD) mice as model of T1D. HucMSC-EVs were isolated from human umbilical cord MSCs and characterized. NOD mice (aged 4 weeks) were administered with HucMSC-EVs or the same volume of phosphate-buffered saline (PBS) via caudal vein injection twice per week. After 8 weeks of treatment, blood, spleen, and pancreatic samples were collected. Mouse blood glucose levels and body weights were measured during treatment, and insulin concentration and inflammatory cytokine levels were analyzed by enzyme-linked immunosorbent assay (ELISA). Hematoxylin and eosin (H&E) staining and immunohistochemistry (IHC) staining were used to evaluate pathological changes in mouse islets. T lymphocyte subsets were evaluated by flow cytometry, while quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot (WB) analyses were used to detect the expression of transcription factor and inflammatory cytokines. Our data indicated that HucMSC-EVs treatment reduced blood glucose levels and increased insulin concentration in NOD mice. Levels of interleukin-2 (IL-2), IL-4, and IL-10 were significantly increased and those of IL-1β and interferon-γ (IFN-γ) significantly decreased in the HucMSC-EVs group. The positive ratio of CD4+ T lymphocyte subsets decreased after intravenous injection of HucMSC-EVs, in which the proportion of Th2 cells increased and that of Th1 decreased. GATA-3 and IL-2, IL-4 and IL-10 expression levels were upregulated in spleen on treatment with HucMSC-EVs, whereas those of T-bet and IFN-γ were downregulated. In addition, more inflammatory cell infiltration was detected in the pancreas of control group mice than those treated with HucMSC-EVs. IHC staining showed that Fas/FasL expression and distribution in control group pancreas were higher than those in the HucMSC-EVs group. Together, our findings indicate that HucMSC-EVs have potential to prevent islet injury via T cell immune responses by adjusting the Th1/Th2 ratio to regulate secretion of inflammatory factors.